The Role of Religion Teacher and Students' Interest in Islamic Spiritual Activites at SMPN 17 Bandung - Sitti Chadidjah; Ajat Syarif Hidayatulloh; Agus Samsul Bassar; Ike Nilawati Norheanah; Rida Nur Farida; Didik Sunandar Asep Saepulmillah (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2020)
Among the roles of religion teachers are directing students and animating religious extracurricular activities. What motivates the students to take part in Rohis (Kerohanian Islam) extracurricular activities is the students' interest in Islamic religious lessons, and the direction from the religion teacher. The purpose of this study, to examine the role of religion teachers and student interests. relation to spiritual activity. This study uses a descriptive quantitative approach with multiple variables. The respondents are active 8th grade students. Data collection through questionnaires, interviews, observation. Then the data was analyzed, then the correlation was calculated using SPSS 20 and then concluded. The find research religion teachers in guiding and motivating, as well as students' interest in learning religion is closely related to the spiritual activities.